If you don’t know, you cannot love: Intercultural contact theory in Indonesian higher education - Logli, Chiara (Journal of International Students, 2026)
This paper examines how cross-cultural encounters shape student learning and development in higher education. Guided by the local adage “If you don’t know, you cannot love,” the study situates intercultural contact theory within Indonesia, the world’s fourth-most populous nation and the largest Muslim community. It highlights the experiences of interisland students, who face linguistic, academic, and social challenges similar to those faced by international students. Using grounded theory methodology, the study encompasses document analysis, observations, surveys, and interviews with 650 administrators, professors, and students at a public university. Region of origin, ethnicity, and religion emerge as key markers of identity. Positive contact is the most memorable aspect of college and is fostered through friendships, student organizations, service learning, and the encouragement of authorities. Negative contact is related to religious fundamentalism, minority resentment, and inadequate institutional support.